A criança diagnosticada com TDAH: e agora, professor? - Oliveira, Carolina Alvim Scarabucci (2017)
This text is the result of a research developed at EducationalStrictu Sensu’s Post Graduation Program at Uberlândia’s Federal University, as a partial requirement to the Educational Master Degree. Our goal was to analyze how school and teachers worked with ADHD’s mutiprofessional diagnosis and how psychopedagogy could help on teacher’s praxis with ADHD’s children. At the first chapter, titled as “A puzzle of a life” we presented my professional construction, which made understand the questions that guided this research.Then, with the intuitto back up theoretically this work’s analysis, we presented the second chapter – “Starting the ADHD’s puzzle: first pieces”. There we found the theoretical support about the disorder and relevant themes that helped to better understand ADHD’s universe: the importance of bounds, specially teacher and students ones, the multiprofessional diagnosis, learning and evaluation concepts based on psychopedagogy understanding, school’s role into ADHD children’s education, the disturb’s medicalization/ pathologisation. To get the research’s data we did semi-structured interviews with teachers, teachers’ supervisors, principals and children diagnosed into their schools. It was also done two projective techniques (Educative Couple and Classroom’s floor plant) with the related children so we could understand how they represented school’s space and their learning bounds. Into the analysis, we decided to use categorical analysis, where the data was divided in 3 parts: “Piece one: the school’s conceptions and work with ADHD’s children”, where we could see which was the professional’s understanding about the disorder and the procedures as an institution to support diagnosed ADHD’s children education; “Piece two: the pedagogical contributions inside the classroom to ADHD’s children”, that presented how pedagogical acts was done inside the classroom to them; and “Piece three: the way ADHD’s children see the actions done to their education and learning process”, which tried to understand how children saw their school and the actions done by them. As an answer to our initial questions, we realized that, even with the diagnosis, school still haven’t have enough information and the right educative formation to help develop an specific work with ADHD’s children, as children don’t realize specifically the actions that has been done to make their learning process better instead of the disorder. Because of it, psychopedagogy would be a bridge to understand learning processes, as to evaluate, understand and act together with the school, the child and the family, bringing a new approach beyond the disorder itself, with better education quality not just for diagnosed children, but to all students in the scholar context.